Nociception in the Glycine Receptor Deficient Mutant Mouse Spastic - Groemer, Teja Wolfgang; Triller, Antoine; Zeilhofer, Hanns Ulrich; Becker, Kristina; Eulenburg, Volker; Becker, Cord Michael (Frontiers in Molecular Neuroscience, 2022)
Glycine receptors (GlyRs) are the primary mediators of fast inhibitory transmission in the mammalian spinal cord, where they modulate sensory and motor signaling. Mutations in GlyR genes as well as some other genes underlie the hereditary disorder hyperekplexia, characterized by episodic muscle stiffness and exaggerated startle responses. Here, we have investigated pain-related behavior and GlyR expression in the spinal cord of the GlyR deficient mutant mouse spastic (spa). In spastic mice, the GlyR number is reduced due to a β subunit gene (Glrb) mutation resulting in aberrant splicing of GlyRβ transcripts. Via direct physical interaction with the GlyR anchoring protein gephyrin, this subunit is crucially involved in the postsynaptic clustering of heteromeric GlyRs. We show that the mutation differentially affects aspects of the pain-related behavior of homozygous Glrbspa/Glrbspa mice. While response latencies to noxious heat were unchanged, chemically induced pain-related behavior revealed a reduction of the licking time and an increase in flinching in spastic homozygotes during both phases of the formalin test. Mechanically induced nocifensive behavior was reduced in spastic mice, although hind paw inflammation (by zymosan) resulted in allodynia comparable to wild-type mice. Immunohistochemical staining of the spinal cord revealed a massive reduction of dotted GlyRα subunit immunoreactivity in both ventral and dorsal horns, suggesting a reduction of clustered receptors at synaptic sites. Transcripts for all GlyRα subunit variants, however, were not reduced throughout the dorsal horn of spastic mice. These findings suggest that the loss of functional GlyRβ subunits and hence synaptically localized GlyRs compromises sensory processing differentially, depending on stimulus modality.